Upaya Meningkatkan Kemampuan Bercerita Melalui Media Gambar Berseri pada Anak Usia 5-6 Tahun di Desa Mertak Kacamatan Pujut Lombok Tengah Tahun 2021 - Ita Lestari; Muazzar Habibi; Ika Rachmayani; Baik Nilawati Astini (Indonesian Publication Center, 2021)
This research is motivated by the low speaking ability of children aged 5-6 years at PAUD Setuwi Jati. The purpose of this study was to find out how to improve children's speaking skills through picture series media. This a qualitative research with a case study approach. The subjects in this study were five children aged 5-6 years at PAUD Setuwi Jati, Mertak Kacan Village, Pujut, Central Lombok. Data were collected through interview, observation and documentation methods. Analysis of the data used is descriptive qualitative analysis. The results showed that children's storytelling skills can be increased through the steps of using serial picture media as follows: children listen to the teacher tell stories using picture series media, children are given the opportunity to tell stories in front of the class using serial image media in turn, after that the children are asked to This sequence of picture stories can be seen from the increase in the storytelling ability of children aged 5-6 years at PAUD Setuwi Jati which occurred, where the score before the action was 134 (27.92%) and in the first cycle the score was 201.5 (41 ,98%) with a maximum score of 480. The increase in score from before the action to the first cycle of action reached 67.5 (14.06%). In the second cycle of action it reached a score of 374 (77.92%) with a maximum score of 480. The increase in storytelling ability from the first cycle to the second cycle reached 172.5 (35.94%).